Studies on The Dissolution and Precipitation Potentials of The Sodium Salts of Organic Acids - Tripathi, B.N. (Asian Journal of Chemistry, 2010)
The dissolution and precipitation potentials of sodium salts of aliphatic organic acids have been calculated on the basis of mechanism of generation of electric potential of electrolytes. The comparison with the experimental data shows that true dissolution potential does not depend on the concentration of the medium, true precipitation potential also does not depend on undercooling.